Вміст греліну у крові хворих на соматотропну недостатність - Большова, О. В.; Самсон, О. Я.; Кульчицька, Н. О.; Вишневська, О. А.; Спринчук, Н. А.; Маліновська, Т. М.; Музь, В. А.; Деревʼянко, Г. А.; Марков, В. В. (Clinical Endocrinology and Endocrine Surgery, 2011)
Height and physical development of a child are determined by endogenous and exogenous factors and regulate by GH system. The aim of this study was to investigate ghrelin action on growth hormone response in GH-sufficient and GH-deficient patients. The level of basal ghrelin in GH-deficient patients was the same in health children. Evaluation of basal ghrelin, two hours after sleeping and ghrelin after clonidine test has been determined in GH-deficient patients. Our results show increase of the ghrelin secretion in control group and in GH-deficient patients after two hours of sleeping. Our data demonstrated that there were no difference between basal ghrelin level in control group and GH-deficient patients. The results revealed decrease ghrelin level after clonidine test in GH-deficient patients.